Interleukin‐13 associates with life‐threatening rhinovirus infections in infants and young children. Issue 6 (17th April 2018) - Caballero, Mauricio T.; Hijano, Diego R.; Acosta, Patricio L.; Mateu, Cecilia G.; Marcone, Débora N.; Linder, Jodell E.; Talarico, Laura B.; Elder, John M.; Echavarria, Marcela; Miller, Eva Kathryn; Polack, Fernando P.; ,
Abstract: Objective: Delineate risk factors associated with severe hypoxemia (O2 sat ≤87%) in infants and children younger than 2 years hospitalized with single pathogen HRV infection. Study Design: Prospective study in a yearly catchment population of 56 560 children <2 years old between 2011 and 2013 in Argentina. All children with respiratory signs and O2 sat <93% on admission were included. HRV infections were identified by reverse transcriptase‐polymerase chain reaction. Epidemiologic, clinical, viral, and immunological risk factors were assessed. Results: Among 5012 hospitalized patients, HRV was detected as a single pathogen in 347 (6.92%) subjects. Thirty‐two (9.2%) had life‐threatening disease. Traditional risk factors for severe bronchiolitis did not affect severity of illness. HRV viral load, HRV groups, and type II and III interferons did not associate with severe hypoxemia. Interleukin‐13 Levels in respiratory secretions at the time of admission (OR = 7.43 (3‐18.4); P < 0.001 for IL‐13 >10 pg/mL) predisposed to life‐threatening disease. Conclusions: Targeted interventions against IL‐13 should be evaluated to decrease severity of HRV illness in infancy and early childhood.